Watching Innovation in Real Time: The Story of ChatGPT and Radiology - Fishman, Elliot K.; Weeks, Bill; Lavista Ferres, Juan M.; Chu, Linda C. (Canadian Association of Radiologists Journal, 2023)
The speed of change in the world of technology has never been as rapid as it is today. For clinicians - as well as clinical researchers - this can translate to both the best of times and the worst of times. While clinicians and clinical researchers become excited by the development of a new computer chip, CT scanner, or vaccine, they know that time will pass before the new technology impacts our daily workflow. That is, until the introduction of large language models like ChatGPT, an offering that allows us to use the technology as it is being developed. This technology – which has been in development for decades - has the chance to impact everything we do at work or at home. And advancements in this technology, fostered by incredible computing power and amounts of data available for learning, occur so quickly that before you can write and publish an article, your descriptions may be one to two versions behind. The story ChatGPT is not one only of imagining what could be but also seeing the change in near real time.